Influence of Pitching Release Location on Ulnar Collateral Ligament Reconstruction Risk Among Major League Baseball Pitchers. Issue 2 (20th February 2019) - Portney, Daniel A.; Buchler, Lucas T.; Lazaroff, Jake M.; Gryzlo, Stephen M.; Saltzman, Matthew D.
Background: Medial ulnar collateral ligament (UCL) reconstruction is a common procedure performed among Major League Baseball (MLB) pitchers. The etiology of UCL injury is complex and is not entirely understood. Hypothesis: To better understand risk factors for requiring UCL reconstruction, we hypothesized that pitchers who eventually undergo the procedure will exhibit different throwing mechanics as measured by pitch-tracking data points, such as velocity and release location. Study Design: Case-control study; Level of evidence, 3. Methods: Pitch-tracking and demographic data were gathered for 140 MLB pitchers who had undergone UCL reconstruction between the 2010 and 2017 seasons. Pitch type, release location, and velocity were compared between the surgical cohort and a matched-control cohort. Results: When compared with controls, the mean pitch release location for pitchers who required UCL reconstruction was 12.2 cm more lateral in the year immediately preceding surgery ( P = .001). Furthermore, within the surgical cohort, the horizontal release location was 3.4 cm more lateral immediately preceding surgery compared with 2 years earlier ( P = .036). Binary logistic regression indicated an odds ratio of 0.51, suggesting a roughly 5% increased odds of UCL reconstruction for every 10 cm of increased lateral release location ( P = .048). Both the surgical and the control cohorts threw similar rates of fastballs and had similar mean pitch velocity and fastball velocity. Control pitchers displayed a significant decrease over time in mean pitch velocity ( P = .005) and mean fastball velocity, while pitchers in the UCL reconstruction cohort did not ( P = .012). Conclusion: Pitch tracking indicates that the mean release point is more lateral in pitchers preceding UCL reconstruction as compared with controls, suggesting that a more lateral pitch release location is an independent risk factor for UCL injury and reconstruction.